3D Rotation‐Trackable and Differentiable Micromachines with Dimer‐Type Structures for Dynamic Bioanalysis. (22nd February 2021) - Lin, Gungun; Liu, Yuan; Huang, Guan; Chen, Yinghui; Makarov, Denys; Lin, Jun; Quan, Zewei; Jin, Dayong
Abstract : Dynamic Bioanalysis In article number 2000205, Gungun Lin, Dayong Jin, and co‐workers develop 3D rotation‐trackable and differentiable micromachines for adaptive manipulation of 3D cell cultures and dynamic analysis of multiple nucleic acids in a single test. These results provide new perspective in designing functional microsystems by exploring the natural variance in the magnetic coupling between colloidal building blocks.